Transformative and community-based participation in collaborative business model experimentation for urban upcycling - van Hees, Marco; Oskam, Inge; Bocken, Nancy (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
<span class="NormalTextRun SCXW62212256 BCX8" data-ccp-charstyle="PLATE - Abstract Zchn" data-ccp-charstyle-defn="{"ObjectId":"2aabb49d-e1f8-55bf-873b-4d16435ccb15|1","ClassId":1073872969,"Properties":[469777841,"Arial",469777842,"Arial",469777843,"SimSun",469777844,"Arial",469769226,"Arial",268442635,"20",469775450,"PLATE - Abstract Zchn",201340122,"1",134233614,"true",469778129,"PLATE-AbstractZchn",335572020,"1",134231262,"true",469777929,"PLATE - Abstract",469778324,"Default Paragraph Font"]}" data-ccp-charstyle-linked-defn="{"ObjectId":"232ed935-540a-5a18-acc7-dc2c97cff6df|1","ClassId":1073872969,"Properties":[469777841,"Arial",469777842,"Arial",469777844,"Arial",469769226,"Arial",268442635,"20",469777843,"SimSun",469775450,"PLATE - Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"PLATE-Abstract",335572020,"1",335559738,"240",335551550,"6",335551620,"6",469777929,"PLATE - Abstract Zchn",469778324,"Normal"]}">Across cities and urban regions in The Netherlands unusual collaborations emerge which aim to develop new circular business models that facilitate product and resource longevity through various upcycling strategies, such as reuse, repair, refurbish, repurpose and/or remanufacture. Municipalities, social entrepreneurs as well as multinational enterprises use various experimentation methods to initiate, test or improve new collaborations in urban upcycling. However, little is known about the role of transformative stakeholder participation in these experiments and how they affect business models for upcycling. Therefore, this study investigates how initiators in urban upcycling use transformative and community-based participatory experimentation to develop collaborative circular business models that facilitate upcycling in a city context. Through a multiple case study approach, this research contributes to literature on circular business model innovation by investigating how practitioners in urban upcycling collaboratively develop, test, implement and scale business models for product and resource longevity in a city context.